(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Limited scientific data regarding the physical condition of junior artistic gymnasts remain a significant issue within the Semarang City Special Sports Class program. In many training environments, evaluations tend to focus primarily on technical skills, while systematic assessments of physical condition are still insufficiently implemented. Comprehensive physical profiling is essential to support evidence-based training programs, optimize athletic performance, and reduce the risk of injury in artistic gymnastics. Therefore, this study aimed to analyze the physical condition profile of junior artistic gymnasts in the Semarang City Special Sports Class using the Gymnastics Functional Measurement Tool (GFMT) in 2026. This study employed a quantitative descriptive research design using a total sampling technique. The participants consisted of six junior artistic gymnasts aged 13–15 years, including three male and three female athletes. Data were collected using the Gymnastics Functional Measurement Tool (GFMT), which measures gymnastics-specific physical capacities such as strength, flexibility, agility, balance, speed, and muscular endurance. The obtained scores were converted into a standardized scale with a maximum score of 100 points and analyzed descriptively using mean values and percentage distributions. The findings revealed that the physical condition of junior male artistic gymnasts was predominantly classified in the moderate category (66.7%), while all junior female artistic gymnasts (100%) were also categorized as moderate. These findings indicate that most gymnasts possess an adequate but not yet optimal level of physical condition. In conclusion, the physical condition profile of junior male and female artistic gymnasts in the Semarang City Special Sports Class is generally categorized as moderate, indicating the need for more targeted and individualized physical conditioning programs to enhance performance development.